On weather signs - Theophrastus. (Philosophia antiqua,, 2007)
On Weather Signs , traditionally ascribed to Theophrastus, contains the most complete list of such signs in antiquity and it was, in this or some very similar form, consulted by Aratus, Vergil (in Georgics I), and Pliny the Elder, as well as by many other authors throughout the Byzantine period. This edition is the first to take account of all the manuscripts and the commentary, the first in over a century, is on a far grander scale than earlier ones by Schneider (1818-21) and Wood (1894), listing almost all parallel texts for each sign. The introduction places the work in the context of its genre and for the first time lays out the details of its manuscript tradition.